Trade Union Power and the Process of Economic Development : The Kenyan Example - Muir, J.; Brown, John (Relations industrielles / Industrial Relations, 1974)
In this paper, the authors discuss some of the policy alternatives available to a Government and a union movement and consider in detail the alternative chosen by one African country, Kenya. Moreover they examine how the Government has sought to reconcile its economic development objectives with granting unions such traditional freedoms as the right to strike, the right to bargain collectively and the right of free association. In doing so they discuss the development of labour legislation in Kenya and examine its effects upon the strike weapon as a source of union power and the effect of strikes on the Kenya economy. Finally they offer some speculations on futur trends of industrial relations in Kenya.